The mediation effect analysis of nurse’s mental health status and burnout under COVID-19 epidemic - Liu, Fuzhi; Zhao, Yanyan; Chen, Yangjia; Tu, Zhuote (Frontiers in Public Health, 2023)
Aim The objective of this study is to investigate the mental health status of nurses during the outbreak of novel coronavirus pneumonia. Additionally, we aim to analyze the relationship between anxiety, depression, and burnout among nurses. The findings will provide a scientific basis for promoting the psychological health of nurses. Methods Using a cross-sectional study, nurses in Quanzhou in May 2020 completed a general information questionnaire, the 7-item Generalized Anxiety Disorder Questionnaire (GAD-7), Patient Health Questionnaire-9 (PHQ-9), and the Maslach Burnout Inventory (MBI). Data analysis was conducted using structural equation model. Results 372 questionnaires were returned, with a response rate of 92.5%. The prevalence of anxiety and depression among the participants were 45.2 and 41.4%, respectively. The prevalence of severe burnout among nurses was found to be 7.3%. There was a correlation between nurses’ anxiety, depression, and job burnout. The correlation coefficients between anxiety and job burnout, depression and job burnout, and anxiety and depression were found to be statistically significant (p < 0.001). Depression plays a mediating role between anxiety and jod burnout (0.584/1.413, 41.3%). Conclusion The COVID-19 epidemic has resulted in moderate to high levels of job burnout among nurses. In this context, depression has been found to play a mediating role in the relationship between anxiety and job burnout. It is imperative for hospital administrators to prioritize the mental health of nurses and the provide necessary support to ensure their well-being.